Islanding detection technique based on the rate of change of frequency (ROCOF) / Nur Wahida Che Jawias - Che Jawias, Nur Wahida (2013)
This thesis presents an islanding detection technique by using the rate of change of frequency (ROCOF) method. The ROCOF was modeled by using PSCAD simulation tool. Islanding is detected when the ROCOF measurement exceeds the threshold limit/setting. A simulation studies on a distribution network with mini hydro generation was carried out to evaluate the ROCOF model.